DISTRIBUTION, ISOLATION AND CHARACTERIZATION OF LYTIC BACTERIOPHAGES AGAINST MULTI-DRUG RESISTANT AND EXTENDED-SPECTRUM OF Î²-LACTAMASE PRODUCING PATHOGENS FROM HOSPITAL EFFLUENTS - Duraisamy Nivas; Nachimuthu Ramesh; Vaithilingam Krishnakumar; Pandiyan Rajesh; Ebenezer King Solomon; Velu Rajesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: To isolate. Screen and characterize an effective phage for MDR and ESBL producing pathogenic bacterial strains. Methods: Bacteriophages were isolated from hospital effluent samples by double layer agar method. Isolated phages were propagated by liquid enrichment technique and its host range was analyzed by double layer agar method. Morphology of the isolated phages was identified by Transmission Electron Microscope (TEM). Genomic and proteomic analysis was confirmed by electrophoresis technique. Results & Discussion: 46 bacteriophages were isolated against 20 different MDR and ESBL strains of those 7 phages (Mm81, Ec84, Ps85, En833, Sal836, Ec8ATCC and Ec8PMG) were selected for further studies. According to the host range analysis result the 7 phage has been shown narrow host range. The phage genomic DNA and structural proteins were analyzed. In addition to based on the TEM analysis two phages viz., Mm81 and Ec84 were belongs to Siphoviridae and Podoviridae family respectively. Present study evaluates the extensive occurrence of phages in the hospital effluent. In addition, this is first report of isolation and characterization of Morganella morganii lytic phage in Tamil Nadu, India. Conclusion: The study highlights the distribution of bacteriophages in the hospital effluent and it gives the therapeutic potential of isolated phages for the treatment of MDR and ESBL Producing Pathogens. Keywords: Phage therapy, Transmission electron microscope, Extended-spectrum of Î²-lactamase, Multi-drug resistant.